PENGARUH GAME EDUCAPLAY TERHADAP HASIL BELAJAR MATEMATIKA PADA MATERI PERKALIAN DAN PEMBAGIAN KELAS II SD NEGERI 36 PALEMBANG - Euis Puspita Sari; Jayanti; David Budi Irawan (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to determine the effect of using the Educaplay Game on the mathematics learning outcomes of grade II students of SD Negeri 36 Palembang on multiplication and division material. The research method used is a quasi-experimental design with a Nonequivalent Control Group Design. This study involved two classes, namely the experimental class using the Educaplay Game and the control class using conventional methods. Data collection was carried out through essay tests before (pretest) and after (posttest) treatment. The results showed an increase in student learning outcomes in the experimental class, with an average pretest score of 75.00 and a posttest of 84.30, while the control class showed an average pretest score of 77.80 and a posttest of 84.30. Data analysis using normality tests, homogeneity tests, and hypothesis tests showed that the use of the Educaplay Game had a significant effect on students' mathematics learning outcomes. Thus, the use of the Educaplay Game as a learning medium can significantly improve students' understanding of multiplication and division materia